2022
DOI: 10.1111/ffe.13644
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fatigue performance of TC4 titanium alloy welded by electron beam welding and laser welding with filler wire

Abstract: This research compared high‐cycle fatigue (HCF) performances of joints of Ti–6Al–4V titanium (TC4) alloy with the thickness of 30 mm welded by vacuum electron beam welding (EBW) and laser welding with filler wire (LWFW) (hereinafter referred to as EBW and LWFW joints). Under test conditions, the fatigue strength of the LWFW joint is only 65% that of the EBW joint. Based on analysis, the main reason is that a larger microhardness gradient is present in the LWFW joint. The average microhardness of the weld metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Fu et al [20] conducted a study on underwater laser welding of titanium alloy and showed that the α martensitic sheet becomes thinner due to a higher cooling rate. Long et al [21] conducted laser welding on TC4 titanium alloy; the results show that a large amount of point-like β phase in the weld will reduce its hardness, and the fatigue strength of laser welded joints is lower than that of vacuum electron beam welded joints. Therefore, under different welding heat sources and cooling conditions, titanium alloys will cause differences in the composition of precipitates, grain size, and microscopic morphology, which affect the mechanical properties of welded joints.…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al [20] conducted a study on underwater laser welding of titanium alloy and showed that the α martensitic sheet becomes thinner due to a higher cooling rate. Long et al [21] conducted laser welding on TC4 titanium alloy; the results show that a large amount of point-like β phase in the weld will reduce its hardness, and the fatigue strength of laser welded joints is lower than that of vacuum electron beam welded joints. Therefore, under different welding heat sources and cooling conditions, titanium alloys will cause differences in the composition of precipitates, grain size, and microscopic morphology, which affect the mechanical properties of welded joints.…”
Section: Introductionmentioning
confidence: 99%